PENGARUH DIGITAL MARKETING DAN WORD OF MOUTH TERHADAP PENINGKATAN BRAND AWARENESS PADA PT. CICIL SOLUSI MITRA TEKNOLOGI DI KOTA SURABAYA - Nabila, Athiyya; Norhabiba, Fitri (The Commercium, 2024)
The purpose of this research is to find out whether digital marketing and word of mouth can influence increasing PT brand awareness. Installment Technology Partner Solutions in the City of Surabaya. The research method uses a descriptive quantitative approach with an online survey method of students at 25 universities in Surabaya who are followers and users of PT. Installment Technology Partner Solutions. Data were analyzed using multiple linear regression to test the hypothesis that digital marketing and word of mouth have a positive influence on increasing brand awareness at PT. Installment Technology Partner Solutions. The results of the research show that digital marketing and word of mouth can influence followers in increasing brand awareness at the recognition stage. It is hoped that this research can contribute to understanding the influence of digital marketing and word of mouth on increasing PT brand awareness. Installment Technology Partner Solutions in the City of Surabaya.